ICTforAg 2024 Technical Report - Koo, Jawoo; Manning, Matt; Angus, Dawn (International Food Policy Research Institute, 2024)
ICTforAg is an annual convening where agricultural stakeholders and technology experts come together to share knowledge, find solutions, and form partnerships to address challenges in agri-food systems across low- and middle-income countries. The main goal of ICTforAg is to grow communities and catalyze meaningful conversations, insights, and collaborations, increase participation of participants from the developing world, promote knowledge sharing and learning, and inspire practitioners to develop inclusive and sustainable ICT solutions. ICTforAg has a strong history since 2015 and owes its success to the contributions made by various organizations to build this community. In 2019, it moved to being hosted by USAID with support from DAI and the Digital Frontiers project. For the first five years, ICTforAg events took place in Washington, DC, with 100–200 attendees annually. The COVID pandemic prompted ICTforAg to become a global online forum, with over 1,500 participants in 2020 and 3,000 in 2022. Speaker numbers also grew, from 40 in 2019 to 145 in 2022. In 2023, CGIAR and DevGlobal, in partnership with USAID Feed the Future and DAI Digital Frontiers, jointly implemented ICTforAg 2023 as a global online conference on November 7-9. ICTforAg 2023 engaged 1,778 attendees and 145 speakers. In 2024, these entities implemented ICTforAg 2024 as a hybrid event on May 28-30 with virtual programming and in-person programming across five locations: New Delhi, India; Nairobi, Kenya; Los Baños, Philippines; Texcoco, Mexico, and Washington,D.C., USA. CGIAR, the world’s largest agricultural research for development organization, and DevGlobal, a world-class professional event management expert, have a track record of jointly organizing online, hybrid, and in-person events and engaging with well-recognized ICTforAg practitioners, academics, researchers, service providers, and users in public and private sectors, including smallholder farmers, across low and middle-income countries. Both organizations are committed to growing ICTforAg communities and catalyzing meaningful conversations, insights, and collaborations.